2007
DOI: 10.1016/j.ydbio.2007.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of palatal epithelial seam disintegration by transforming growth factor (TGF) β3

Abstract: TGFbeta3 signaling initiates and completes sequential phases of cellular differentiation that is required for complete disintegration of the palatal medial edge seam, that progresses between 14 and 17 embryonic days in the murine system, which is necessary in establishing confluence of the palatal stroma. Understanding the cellular mechanism of palatal MES disintegration in response to TGFbeta3 signaling will result in new approaches to defining the causes of cleft palate and other facial clefts that may resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 67 publications
7
94
0
2
Order By: Relevance
“…This normalization included an increase in MEE cell proliferation and a decrease in MES cell death, which have never been reported amongst the activities of TGF-␤ 3 [Murillo et al, 2009;Del Río et al, 2010]. Therefore, during palate development, TGF-␤ 3 , far from only inducing opposing MEE adhesion [Gato et al, 2002;Martínez-Sanz et al, 2008], MES cell death [Martínez-Álvarez et al, 2000b;Murillo et al, 2009] and epithelial-mesenchymal transformation [Ahmed et al, 2007], also appears to be an important regulatory agent of the mechanisms causing palatal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…This normalization included an increase in MEE cell proliferation and a decrease in MES cell death, which have never been reported amongst the activities of TGF-␤ 3 [Murillo et al, 2009;Del Río et al, 2010]. Therefore, during palate development, TGF-␤ 3 , far from only inducing opposing MEE adhesion [Gato et al, 2002;Martínez-Sanz et al, 2008], MES cell death [Martínez-Álvarez et al, 2000b;Murillo et al, 2009] and epithelial-mesenchymal transformation [Ahmed et al, 2007], also appears to be an important regulatory agent of the mechanisms causing palatal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…These, in parallel with the transcription factors Snai1 and Snai2, promote MES apoptosis and disintegration. 6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups.…”
Section: Discussionmentioning
confidence: 64%
“…In mice, Tgfb3 is involved in mediating palatal fusion via repressing E-cadherin transcription, leading to epithelial mesenchymal transformation (EMT) and cell migration (Dudas et al, 2004;Nawshad and Hay, 2003;Nawshad et al, 2007). Under the influence of Tgfb3, the murine palatal MEE cells undergo cell cycle arrest, cell migration and apoptosis to generate palatal confluency (Ahmed et al, 2007). In comparison, our data shows that the role of zebrafish tgfb3 in palatogenesis differs from murine Tgfb3.…”
Section: Role Of Tgfb3 In Zebrafish Palatogenesismentioning
confidence: 68%
“…Lef1 in turn binds to the E-cadherin promoter and represses its transcription, leading to epithelial mesenchymal transformation (EMT) and cell migration . Furthermore, MEE cells isolated from mice can chronologically undergo cell cycle arrest, cell migration and apoptosis to generate palatal confluency in response to TGFb3 treatment (Ahmed et al, 2007).…”
Section: Introductionmentioning
confidence: 99%